The effect of musical sensory orientation training in improving consciousness level in patients with disorders of consciousness: a pilot study - Gu, Jiayi; Long, Wei; Zeng, Siqin; Qin, Liang; Dong, Yi; Fang, Cuini; Zhang, Xiaoying (Frontiers in Neuroscience, 2025)
IntroductionMusical sensory orientation training (MSOT) is an innovative technique to improve the state of consciousness and cognitive function. Compared with traditional arousal therapies, MSOT offers a non-invasive, safe, and easily operable alternative with no side effects. This study aimed to conduct a preliminary investigation into the effect of MSOT in improving consciousness levels in patients with DoC (Disorders of Consciousness), as well as the feasibility of its clinical application, thereby providing reference for future large-sample randomized controlled studies.MethodsWe recruited 42 participants between March 2024 to March 2025, dividing them into two groups: a control group of 21 patients who received conventional treatment for DoC and watched videos of family/friends’ activities and short videos, and an intervention group of 21 patients who received MSOT along with conventional treatment. Patients in both groups were assessed at baseline, week 5 and week 8 of the intervention.ResultsThe MSOT group showed significant improvement in Coma Recovery Scale—Revised (CRS-R) subscale and total scores over time (baseline, week 5, week 8). At week 8, the MSOT group demonstrated significantly higher CRS-R scores in communication function and arousal level compared to the control group. Behavioral observations in the MSOT group revealed significantly higher frequencies of name response, sound source tracking, and command-following behaviors.ConclusionThe results of this study demonstrate that MSOT exhibits certain effect in improving consciousness levels in patients with DoC and demonstrates feasibility in clinical implementation. Extending the intervention duration in future studies may amplify its therapeutic effects.